Comparison of wheat-based rotation systems and monocropping systems under dryland Mediterranean conditions - Tekin, Servet; Yazar, Attila; Barut, Hatun (International Journal of Agricultural and Biological Engineering, 2017)
Mono-cropping systems consisting of general low-yielding cereals are crucial productivity constraints in dry areas of the Mediterranean region. A crop rotation consisting of quinoa (Chenopodium quinoa Willd.)–wheat (Triticum aestivum L)-chickpea (Cicer arietinum) was compared with monocropping in the Mediterranean region of Turkey. A four year crop rotation trial was set up in Adana, Turkey. A total of nine crop rotation systems of Quinoa (Q), chickpea (L) and wheat (W) were considered in this study. The four year results revealed that there was significant difference in grain and biomass yields, but no significant difference in plant height, harvest index, and 1000 grain weight of wheat among the treatments in crop rotation except number of grains per spike and soil organic matter. Continuous wheat and chickpea-wheat-chickpea-wheat (LWLW) produced significantly greater grain yield in 2010/2011 and 2011/2012. QWLW and QWQW rotation produced significantly lower biomass yield in 2008/2009. The maximum biomass yield of LWLW rotation resulted in 2011/2012 growing season. Therefore, the effect of previous crop on wheat grain and biomass yield in the four years of the rotation study was significantly different. In the long run, the favorable effects of legume-based rotations on crop yields and water productivity are apparent. Keywords: crop rotation system, monocropping system, quinoa, Chenopodium quinoa, chickpea, dryland, yield DOI: 10.25165/j.ijabe.20171005.3443 Citation: Tekin S, Yazar A, Barut H. Comparison of wheat-based rotation systems and monocropping systems under dryland Mediterranean conditions. Int J Agric & Biol Eng, 2017; 10(5): 203–213.